2012
DOI: 10.1080/15205436.2011.568317
|View full text |Cite
|
Sign up to set email alerts
|

Subconscious Gatekeeping: The Effect of Death Thoughts on Bias Toward Outgroups in News Writing

Abstract: This study contributes to gatekeeping theory by examining the importance of individual-level subconscious psychological factors in news story fact selection, specifically whether the thought of death increases biased writing toward outgroups. An experiment (N ¼ 79), based on terror management theory from social psychology, indicated that college journalists primed to think about death injected into their news stories 66% more negative facts toward a rival university than those in a control condition. Implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…By conceptually replicating this idea in three independent MRS contexts, we built on previous research theorizing on the role of implicit and explicit attitudes in the media context (e.g., Ewoldsen, Rhodes, & Fazio, ; Goodall, ). In fact, MRS research has already acknowledged that news users are typically not aware of processes governing their choice decisions (Knobloch‐Westerwick, ) and that MRS decision makers “consciously or subconsciously inject bias” (Cuillier, , p. 4). However, this study goes beyond previous research by thoroughly specifying the processes underlying selection decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By conceptually replicating this idea in three independent MRS contexts, we built on previous research theorizing on the role of implicit and explicit attitudes in the media context (e.g., Ewoldsen, Rhodes, & Fazio, ; Goodall, ). In fact, MRS research has already acknowledged that news users are typically not aware of processes governing their choice decisions (Knobloch‐Westerwick, ) and that MRS decision makers “consciously or subconsciously inject bias” (Cuillier, , p. 4). However, this study goes beyond previous research by thoroughly specifying the processes underlying selection decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Figure visualizes this assumption by letting one door of the swing gate be controlled by implicit attitudes. Although previous MRS research has already acknowledged the importance of “deeply held, often subconscious, biases” (Shoemaker & Vos, , p. 49; see also Cuillier, ), there is a lack of empirical evidence.…”
Section: Implicit and Explicit Attitudesmentioning
confidence: 99%
“…Indeed, Cuillier (2012) found that college joumalists incorporated more negative facts about an outgroup into a news story following MS than following a control prime. Media reports also often include threats to people's worldview and thereby undermine people's anxiety buffer, which is especially needed in times of threat.…”
Section: Self-perpetuation Of Violent Intergroup Conflictsmentioning
confidence: 96%
“…selecting what information to cover in the news media unconsciously, while still adhering to the goal of steering clear of bias (Cuillier, 2012). Because it would be impossible for the news media to know about and report on everything going on in the world, country, and local community, such decisions are, to some extent, unavoidable and integral to the news-making process.…”
Section: Gatekeeping Suggests That Journalists and Editors Participatmentioning
confidence: 99%
“…Some scholars have identified a hierarchical model of outside influences that are likely to have the greatest impact on the gatekeeping decisions of journalists. Included in these hierarchical pressures are things such as the organization's social environment, editors, professional and social norms, and journalistic processes (Cuillier, 2012;Shoemaker & Reese, 1996). Perhaps somewhat surprisingly, the outside pressures actually play a larger role in influencing news content than do the personal standpoint, opinions, and gender of journalists (Bleske, 1997;Cassidy, 2006;Shoemaker & Reese, 1996).…”
Section: Gatekeeping Suggests That Journalists and Editors Participatmentioning
confidence: 99%